Prevalence and Characteristics of Shellfish Allergy in the Pediatric Population of the United States - Wang, Helen T. (J Allergy Clin Immunol Pract, 2020)
BACKGROUND: Shellfish allergy (SA) is one of the most common food allergies causing anaphylaxis in adults and children. There is limited data showing the prevalence of SA in US children. OBJECTIVE: To determine the prevalence and reaction characteristics of SA in the US pediatric population. METHODS: A cross-sectional food allergy prevalence survey was administered via phone and web by the National Opinion Research Center at the University of Chicago from 2015–2016. Point prevalence SA estimates, complex survey weighted proportions and 95% confidence intervals were determined. Relative proportions of demographic characteristics were compared using weighted Pearson chi-square statistics. RESULTS: The prevalence of SA was 1.3% (95% CI 1.1–1.5) with more children allergic to crustacean (1.2%; 95% CI 1.0–1.3) than mollusk (0.5%; 95% CI 0.4–0.6). Mean ages of shellfish, crustacean, and mollusk allergy diagnosis were 5.0 (95% CI, 4.4–5.6), 5.1 (95% CI, 4.6–5.6), and 7.7 years old (95% CI, 5.7–9.7), respectively. More than half (54.9%; 95% CI 48.1–61.4) of SA pediatric patients had >1 lifetime food allergy related emergency room visit but only 45.7% (95% CI 39.2–52.4) carried an epinephrine auto-injector. Children with shellfish allergy were more likely to be Black/Hispanic/Latino, and have comorbid asthma, allergic rhinitis or a parental history of asthma, environmental or other food allergies (p<0.001). CONCLUSION: The epidemiology of SA in the US pediatric population shows crustacean allergy is more common than mollusk allergy. A disparity in SA children and epinephrine auto-injector carriage exists. Results from this study will lead to increased awareness of the need for detailed histories, specific diagnostic tests, and rescue epinephrine for anaphylaxis in US children with SA.